The presentation of crime in news media - Kesić Dušan B. (Sociološki Pregled, 2020)
Crime reporting occupies a central position in the print and broadcast media agenda. The key thing about media reporting on crime is the question of the impact that the dominant media discourse on crime has on the public perception of this phenomenon. The aim of this paper is to make an insight at how crime is presented in the media, to identify the criteria that guide the selection of crime news, and finally, the impact that media presentation of crime has on the audience. Researches on media reporting on crime suggest that the over-representation of violent crime affects the media's construction of crime, by presenting this phenomenon as dominantly violent.